2008
DOI: 10.1107/s1744309108025359
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the catalytic trimer ofMethanococcus jannaschiiaspartate transcarbamoylase in an orthorhombic crystal form

Abstract: PDB Reference: aspartate transcarbamoylase, 3e2p, r3e2psf.Crystals of the catalytic subunit of Methanococcus jannaschii aspartate transcarbamoylase in an orthorhombic crystal form contain four crystallographically independent trimers which associate in pairs to form stable staggered complexes that are similar to each other and to a previously determined monoclinic C2 form. Each subunit has a sulfate in the central channel. The catalytic subunits in these complexes show flexibility, with the elbow angles of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Three are structures of the isolated catalytic trimer [ 40 , 41 ]. Seventeen structures are from organisms other than E. coli , six are from the hyperthermophilic archaeons, Pyrococcus abyssi [ 42 ], Sulfolobus acidocaldarius [ 43 , 44 ] and Methanococcus jannaschii [ 45 , 46 , 47 ], and one is from the γ-division of proteobacteria Moritella profunda , a psychrophilic deep sea bacterium [ 48 ]. S. acidocaldarius ATCase was solved as the dodecameric holoenzyme, while the structure from P. abyssi is of the catalytic trimer complexed with the bisubstrate analogue, N -phosphonacetyl- l -aspartate (PALA).…”
Section: Structures Deposited In the Protein Data Bank (Pdb)mentioning
confidence: 99%
“…Three are structures of the isolated catalytic trimer [ 40 , 41 ]. Seventeen structures are from organisms other than E. coli , six are from the hyperthermophilic archaeons, Pyrococcus abyssi [ 42 ], Sulfolobus acidocaldarius [ 43 , 44 ] and Methanococcus jannaschii [ 45 , 46 , 47 ], and one is from the γ-division of proteobacteria Moritella profunda , a psychrophilic deep sea bacterium [ 48 ]. S. acidocaldarius ATCase was solved as the dodecameric holoenzyme, while the structure from P. abyssi is of the catalytic trimer complexed with the bisubstrate analogue, N -phosphonacetyl- l -aspartate (PALA).…”
Section: Structures Deposited In the Protein Data Bank (Pdb)mentioning
confidence: 99%
“…Currently, the crystal structures of bacterial ATCases from Escherichia coli (Honzatko et al, 1982), Bacillus subtilis (Stevens et al, 1991), Pyrococcus abyssi (Van Boxstael et al, 2003), Sulfolobus acidocaldarius, Moritella profunda (De Vos et al, 2004, 2007 and Methanococcus jannaschii (Vitali & Colaneri, 2008), and of the A. aeolicus ATCase-DHO complex (Zhang et al, 2009) have been reported. In the present study, we report the expression, purification, crystallization and preliminary X-ray analysis of TcATCase.…”
Section: Introductionmentioning
confidence: 99%